2011
DOI: 10.21236/ada537920
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Decision Support System for Workforce Forecast

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 173 publications
(200 reference statements)
0
1
0
Order By: Relevance
“…The results of the experiment showed that the application of fuzzy logic in this method had improved the precision, perceived quality and the performance on the metadata field. Wan et al [11] presented an intelligent decision system for stock managers based on the fuzzy inference which can assist in deciding that people buy, sell or hold their stock. Fuzzy-based clustering was introduced in another study [12].…”
Section: A Fuzzy Logic Methodsmentioning
confidence: 99%
“…The results of the experiment showed that the application of fuzzy logic in this method had improved the precision, perceived quality and the performance on the metadata field. Wan et al [11] presented an intelligent decision system for stock managers based on the fuzzy inference which can assist in deciding that people buy, sell or hold their stock. Fuzzy-based clustering was introduced in another study [12].…”
Section: A Fuzzy Logic Methodsmentioning
confidence: 99%